Thomas Alva Edison, an American myth - Wachhorst, Wyn (MIT Press, 1961)
Edison was born in Milan, Ohio, February 11, 1847, and died October 18, 1931 at 84 years of age. His Edison Electric Light Company was the predecessor of the General Electric Co. While operating this company, and later working at laboratories in Menlo Park and West Orange, New Jersey, he was credited with patents for over one thousand inventions.